Conversion of methane to organic acids is a widely found trait among gammaproteobacterial methanotrophs of freshwater lake and pond ecosystems - Khanongnuch, Ramita; Mangayil, Rahul; Rissanen, Antti Juhani (American Society for Microbiology, 2023)
Aerobic gammaproteobacterial methanotrophs (gMOB) are key organisms controlling methane fluxes at the oxic-anoxic interfaces of freshwater ecosystems. Under hypoxic environments, gMOB may shift their aerobic metabolism to fermentation, resulting in the production of extracellular organic acids. We recently isolated a gMOB strain representing the Methylobacter spp. of boreal lake water columns (i.e., Methylobacter sp. S3L5C) and demonstrated that it converts methane to organic acids (acetate, formate, malate, and propionate) under hypoxic conditions. Annotation for putative genes encoding organic acid production within the isolate’s genome and in environmental metagenome-assembled genomes (MAGs) representing Methylobacter spp. suggests that the potential for methane conversion into organic acids is widely found among Methylobacter spp. of freshwater ecosystems. However, it is not known yet whether the capability to convert methane to organic acids is restricted to Methylobacter spp. or ubiquitously present among other freshwater gMOB genera. Therefore, we isolated representatives of two additional gMOB genera from the boreal lake water columns, i.e., Methylomonas paludis S2AM and Methylovulum psychrotolerans S1L, and demonstrated similar bioconversion capacities. These genera could convert methane to organic acids, including acetate, formate, succinate, and malate. Additionally, S2AM produced lactate. Furthermore, we detected genes encoding organic acid production within their genomes and in MAGs representing Methylomonas spp. and Methylovulum spp. of lake and pond ecosystems. Altogether, our results demonstrate that methane conversion to various organic acids is a widely found trait among lake and pond gMOB, highlighting their role as pivotal mediators of methane carbon into microbial food webs of freshwater lake and pond ecosystems.
Keywords: greenhouse gas; climate change; food web; extracellular metabolites; bioconversion; psychrophilic; psychrotolerant